Restoration and reform, 1153-1165 : recovery from civil war in England - White, Graeme J (Cambridge University, 2013)
This book examines the processes by which effective royal government was restored in England following the civil war of Stephen's reign. It questions the traditional view that Stephen presided over 'anarchy', arguing instead that the king and his rivals sought to maintain the administrative traditions of Henry I, leaving foundations for a restoration of order once the war was over.